Narrowing the gap in the access to justice for child victims in postconflict societies: an analysis stemming from the construction of child soldiers in international law and policy - Bameka, Christelle Molima (International journal of transitional justice, 2023)
A controversial approach characterizes international law and policy on children affected by armed conflict: it is much more concerned with child soldiers’ victimization than with their victims’ situation. This approach leads to (1) the prioritization of the former over the child victims of their crimes before judicial and non-judicial mechanisms and (2) a significant disparity in how international law and policy respond to the victimization of war-affected children in the presence of those categorized as ‘child soldiers.’ To narrow this gap, this article explores the potential of defining child soldiers as victims who victimize during trials. It does so by discussing the practice observed in local juvenile courts in the North and South Kivu provinces in the Democratic Republic of Congo.